Serum SARS-COV-2 Nucleocapsid Protein: A Sensitivity and Specificity Early Diagnostic Marker for SARS-COV-2 Infection - Li, Tao; Wang, Li; Wang, Huihui; Li, Xuemei; Zhang, Shubing; Xu, Yuanhong; Wei, Wei (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: To explore the diagnostic value of serum severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleocapsid (N) protein assay in the early stage of SARS-COV-2 infection. Methods: Serum N protein in SARS-COV-2 infected patients and non-SARS-COV-2 infected population was measured by enzyme-linked immunosorbent assay (ELISA) double antibody sandwich assay. Colloidal gold immunochromatography assay is used to detect serum N protein antibodies in the above population. Results: 50 cases of SARS-CoV-2 nucleic acid positive and SARS-CoV-2 antibody negative patients had a serum N protein positive rate of 76%. 37 samples of patients with serum SARS-CoV-2 antibody positive after infection had a serum SARS-CoV-2 N protein positive rate of 2.7%. Serum N protein test results of 633 non-SARS-COV-2 infected patients including pregnant women, other respiratory infections, and increased rheumatoid factor were all negative, having a serum N protein concentration less than 10.00 pg/mL, with a specificity of 100%. Using SPSS 19.0 to calculate the receiver operating characteristic curve, the area under the curve was 0.9756 (95% confidence interval 0.9485-1.000, p <0.0001), sensitivity and specificity were 92% (95% confidence interval 81.16% to 96.85%) and 96.84% (95% confidence interval 95.17% to 97.15%). The best CUTOFF value is 1.850 pg / mL. Conclusion: The measurement of serum SARS-COV-2 N protein has a high diagnostic value for the infected patients before the antibody appears, and shortens the window period of serological diagnosis. The laboratory needs to establish an individual CUTOFF value according to purpose of the application.